2018
DOI: 10.1016/j.bbi.2017.08.027
|View full text |Cite
|
Sign up to set email alerts
|

The microbiota influences cell death and microglial colonization in the perinatal mouse brain

Abstract: The mammalian fetus develops in a largely sterile environment, and direct exposure to a complex microbiota does not occur until birth. We took advantage of this to examine the effect of the microbiota on brain development during the first few days of life. The expression of anti- and pro-inflammatory cytokines, developmental cell death, and microglial colonization in the brain were compared between newborn conventionally colonized mice and mice born in sterile, germ-free (GF) conditions. Expression of the pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 90 publications
(133 reference statements)
3
57
2
1
Order By: Relevance
“…Data from males and females were combined in all analyses. Previous studies from our lab found no sex differences in cell death during the time points analyzed here (Ahern et al, 2013;Mosley et al, 2017a;Castillo-Ruiz et al, 2018a;2018b). We, and others, also have not found sex differences in microglial number or morphology in newborn mice (Strahan et al, 2017;Hanamsagar et al, 2017;Castillo-Ruiz et al, 2018a), although such sex differences have been reported in rats (Schwarz et al, 2012;VanRyzin et al, 2019) and adult mice (Hanamsagar et al, 2017;Guneykaya et al, 2018;Villa et al, 2018).…”
Section: Statisticscontrasting
confidence: 56%
See 1 more Smart Citation
“…Data from males and females were combined in all analyses. Previous studies from our lab found no sex differences in cell death during the time points analyzed here (Ahern et al, 2013;Mosley et al, 2017a;Castillo-Ruiz et al, 2018a;2018b). We, and others, also have not found sex differences in microglial number or morphology in newborn mice (Strahan et al, 2017;Hanamsagar et al, 2017;Castillo-Ruiz et al, 2018a), although such sex differences have been reported in rats (Schwarz et al, 2012;VanRyzin et al, 2019) and adult mice (Hanamsagar et al, 2017;Guneykaya et al, 2018;Villa et al, 2018).…”
Section: Statisticscontrasting
confidence: 56%
“…Previous studies from our lab found no sex differences in cell death during the time points analyzed here (Ahern et al , ; Mosley et al , ; Castillo‐Ruiz et al , ; ). We, and others, also have not found sex differences in microglial number or morphology in newborn mice (Strahan et al , ; Hanamsagar et al , ; Castillo‐Ruiz et al , ), although such sex differences have been reported in rats (Schwarz et al , ; VanRyzin et al ., ) and adult mice (Hanamsagar et al , ; Guneykaya et al , ; Villa et al , ). Two‐tailed independent t‐tests were used to compare saline and clodronate liposome groups for density of Iba1+ and AC3+ cells.…”
Section: Methodscontrasting
confidence: 39%
“…Together with birth timing, other extrinsic factors also modulate cell death. For example, delivery mode (Castillo-Ruiz et al, 2018b) and the exposure to a microbiota at birth (Castillo-Ruiz et al, 2018a) affect the magnitude of cell death in the neonatal mouse brain. Moreover, effects are regionally specific in both cases, as in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated overall brain size by outlining the left side of the entire FB from the point where the medial border of the anterior commissure is located ventral to the tip of the lateral ventricle to the rostral most appearance of the dorsomedial nucleus of the hypothalamus (Paxinos et al, 2007, their Figs. 57-70 of the developing mouse brain atlas) as described previously (Castillo-Ruiz et al, 2018a).…”
Section: Brain Regions and Total Fb Volumementioning
confidence: 99%
“…For example, microglia from E18.5 embryos from GF mothers show an increased density in various brain regions, with increased numbers of microglia exhibiting a ramified morphology, indicative of a resting state. Altered microglial morphology and density, as well as attenuated inflammatory responses, are also observed in offspring of GF dams immediately after birth, a time when microglia typically exhibit an activated phenotype (Castillo-Ruiz et al, 2018).…”
Section: Maternal Microbiota Shapes Prenatal Microglial Maturation Anmentioning
confidence: 99%